Career Services in Higher Education: A Descriptive Study - Belén Suárez Lantarón (Red U, 2013)
In recent decades, the higher and more flexible specialization and the emergence of new labor forms contribute significantly to set a new stage for career guidance. The labor market has been modified creating new ways of working. It demands a new type of employee that has interpersonal and intrapersonal skills and also with willingness to move in a global labor market.